Sustainability Analysis of Millennial Farmers' Development in Greater Malang - Rahajeng Kumara Ardyanti; Mangku Purnomo; Asihing Kustanti (Jurnal Ilmu Sosial dan Humaniora, 2024)
Millennial farmers growing in the digital era have a strong ability to leverage the power of networks and social technology. In recent times, the agricultural scenery in Greater Malang has experienced substantial changes due to the heightened engagement of millennial farmers. Recognizing the importance of this phenomenon, our research aims to conduct a comprehensive sustainability analysis of the factors driving the rapid progress of millennial farmers in Greater Malang. The study seeks to uncover the interplay among various factors, including technology adoption, social and economic dynamics, environmental considerations, and policy frameworks. This type of research is quantitative descriptive. The analysis technique employed is Multidimensional Scaling (MDS). The sustainability assessment findings for Millennial Farmer Development in Greater Malang indicate a reasonably sustainable status, with an index score of 51.27. Among the five dimensions ecology, social, economic, technology, and institutional the social aspect demonstrates the highest sustainability index at 54.92, falling into the fairly sustainable category.